Partial Discharge Characterization of HFO(E) Gas Using Ultra-High Frequency (UHF) Antenna for Medium Voltage Switchgear Application - Ahmed, Rizwan; Abd-Rahman, Rahisham; Ullah, Zahid; Ullah, Rahmat; Mohd Yousof, Mohd Fairouz; Ullah, Kaleem (Ieee Acces, 2024)
The most frequent and dangerous hazard to the electrical insulation of high voltage (HV) and high field (HF) equipment is partial discharges (PD). The development of PD activity is both a cause and an indicator of insulation degradation, which could ultimately lead to insulation breakdown. For electrical power equipment to operate safely and dependably, continuous and efficient PD monitoring must be conveniently performed to prevent associated damages and any harm to electrical power equipment. This work presents the design of a new UHF antenna for detecting PD in medium-voltage gas-insulated applications. The working frequency band of the proposed UHF antenna is 370 MHz–1300 MHz, which translates into a total bandwidth of 930 MHz UHF frequency band. Over the whole operating frequency of the antenna, the return loss is less than -10dB. Recently, an eco-friendly insulating gas, HFO1336mzz(E), is considered to be a good substitute for sulfur hexafluoride (SF6) in medium-voltage gas-insulated equipment (MV-GIE). The HFO(E) gas in a mixture with CO2 can reach the dielectric strength of SF6 gas. Hence, the HFO(E)/CO2 gas mixture’s partial discharge properties are systematically investigated in this research work. In particular, a detailed examination focuses on the partial discharge extinction voltage (PDEV) and partial discharge inception voltage (PDIV) under varying electric field conditions at different gas pressure levels and mixing ratios. The PDIV of the HFO(E)/CO2 gas mixture exhibited a linear-saturation rising pattern with both mixing ratio and gas pressure, mirroring the trend observed in SF6 when the HFO(E) gas concentration ranged between 25% and 30%.